Covid-19 and Pre-Morbid Lifestyle-Related Risk Factors-A Review - Ifeoma N Monye; Moyosore Taiwo Makinde; Tijani Idris Ahmad Oseni; Abiodun Bamidele Adelowo; Samba Nyirenda (SAGE Publishing, 2023)
Since its outbreak in December 2019 in China, COVID-19 has spread like wild fire to affect many communities of the world. The high infectivity and case fatality rates of the disease among the general population and the severely ill patients respectively drew the attention of the global community. Our review showed that socio-demographic and lifestyle-related risk factors and underlying comorbid diseases were directly and indirectly associated with increased susceptibility and severity of COVID-19. These factors included older age (⩾60 years), male gender, and ethnic minority groups (especially blacks), smoking, low serum level of vitamin D, unhealthy diet, physical inactivity (with poor exposure to sunlight), overweight/obesity, high blood pressure/hypertension, high blood cholesterol, cardiovascular diseases (like stroke and coronary heart disease), diabetes mellitus, chronic obstructive pulmonary disease, chronic kidney disease, chronic liver disease, and some cancers (like leukemia, lymphoma, or myeloma). The literature further revealed that the clinical progression of the majority of these associated risk factors can be modified through effective and comprehensive risk reduction through healthy living and lifestyle modification. COVID-19 preventive and treatment guidelines that give adequate attention to risk reduction and healthy lifestyle among people-either in the pre-, peri-, or post-COVID-19 stage, should be developed by public health policymakers and clinicians. This will play a significant role in the global effort to combat the pandemic, and reduce its negative impact on the life expectancy and socio-economic development of the world particularly in low- and middle-income countries (LMICs).